Ceramic paste for glazing

By introducing lithium and strontium into dental restoration materials, combined with glass powder and cellulose ether, the hardness, strength and fracture toughness of ceramic paste are improved, and the chemical solubility problem of existing ceramic paste in acidic environments is solved, and the chemical solubility problem of existing ceramic paste in acidic environments is improved. The stability and aesthetics of dental restoration materials.

CN119320236APending Publication Date: 2025-01-17AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411495440.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing dental restoration material ceramic paste has shortcomings in hardness, strength and fracture toughness, especially in acidic environments, which affects its effectiveness in oral use.

Method used

The ceramic paste with lithium element (Li2O) and strontium element (SrO) as the main inorganic components is used, and the linear expansion coefficient and component ratio of the ceramic paste are combined with glass powder and cellulose ether to adjust the linear expansion coefficient and component ratio of the ceramic paste to improve hardness, strength and fracture toughness. Reduce chemical solubility.

Benefits of technology

The high Vickers hardness, bending strength and fracture toughness of ceramic paste after sintering is achieved, while reducing chemical solubility and improving its stability and use effect in an acidic environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses ceramic paste for glazing, and belongs to the field of biological materials, the ceramic paste for glazing is composed of organic components and inorganic components, after sintering, the Vickers hardness of the ceramic paste for glazing is not less than 3 GPa, and the chemical solubility is not greater than 70 [mu] g / cm < 2 >; the ceramic paste contains a lithium element and a strontium element; the inorganic component is glass powder, the organic component is an organic solvent and a dispersing agent, and based on 100 parts by mass of glass powder, the mass part of the organic solvent is 20-100 parts; the mass part of the dispersing agent is 0.01 to 5 parts. The ceramic paste disclosed by the invention can form a bright glaze surface after being sintered, and has excellent physical and chemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomaterials, and in particular relates to a ceramic paste for glazing. Background Art

[0002] Teeth are important tissues of the human body. Some people often suffer from caries, missing or broken teeth due to lack of hygiene. At this time, it is necessary to repair the affected area to get a good tooth again.

[0003] At present, the main dental restoration materials are metal porcelain and all-ceramic. Metal porcelain uses metal as the base, and the surface is covered with decorative porcelain to achieve an aesthetic effect. All-ceramic materials mainly include zirconium oxide and lithium disilicate glass-ceramic, and the outer surface is glazed (glazing is another form of decorative porcelain) to provide aesthetic performance, making the restored teeth look more realistic and beautiful. The earliest decorative porcelain on the market was mainly sold in the form of powder. Dental technicians need to mix it with liquid and mix it to a suitable viscosity before operating on the restoration. With the development of technology, decorative porcelain sold in the form of paste, that is, ceramic paste for glazing (also called paste), has appeared. Dental technicians no longer need to mix powder and liquid into a paste, but only need to add a small amount or no diluent according to the consistency of use to achieve the operation on the restoration. It reduces the workload of dental technicians, and this form of product is increasingly favored by dental technicians.

[0004] Patent No. WO2022118905A1 discloses a paste-like dental glass composition, which contains glass powder and an organic solvent having less than 2 hydroxyl groups in the molecule and a viscosity of less than 2500mPa·s at 20°C and more than 3 hydroxyl groups in the molecule. The glass composition can accurately adjust the color tone, will not leave organic matter after calcination, will not change color, and the dripping of the paste is suppressed, the operability is good, and the color tone of the porcelain material can be easily adjusted. In addition, the paste will not dry out during filling, and the operability is also excellent.

[0005] Patent No. WO2024024661A1 discloses a dental porcelain paste, which contains a cationic surfactant, glass powder and alcohol. The dental porcelain paste has the advantages of not solidifying even if stored for a long time and being easily restored to the state when it was just prepared. The dental porcelain paste also has the advantages of not changing color and not losing transparency after firing.

[0006] A Chinese patent with publication number CN111467246A discloses a dental ceramic paste, comprising glass powder, hydrophobic microparticle silica modified by a silane coupling agent, and an organic solvent. The prior art introduces hydrophobic silica to enable the paste to remain in a paste state for a long time, and since no additional polymer components are added, the paste is sintered to form a film at 650-850° C., thereby solving the problem that the polymer components may cause carbonization, blackening, or bubbles.

[0007] The above patents have made innovations in the operability, long-term placement stability, and effects after firing of ceramic pastes, all of which focus on improving the user experience of technicians, but none of them have studied the improvement of the physical and chemical properties of the paste. As a dental material, it can have high hardness, high strength, high fracture toughness and low chemical solubility, which has a positive impact on the effect of use in the mouth. Therefore, on the basis of ensuring that there are no problems with the use of the technician, the patent of this invention has innovatively studied the improvement of the hardness, strength, fracture toughness and other properties of the ceramic paste, so as to improve the effect of use in the patient's mouth. Summary of the invention

[0008] In view of the above problems, the present invention provides a ceramic paste for glazing, which can form a bright glaze surface after sintering, has high hardness, high strength and high fracture toughness, and has low chemical solubility in an acidic environment.

[0009] In order to achieve the above-mentioned purpose of the invention, the technical solution adopted by the present invention is: a ceramic paste for glazing, wherein the glazing paste is composed of organic components and inorganic components.

[0010] Specifically, in the present invention, in addition to the organic and inorganic components mentioned above, the ceramic paste may also include other optional components, such as water, pigments, fluorescent agents, pH regulators, mildew inhibitors, etc. As long as the added other optional components do not impair the use effect of the present invention.

[0011] In the present invention, after the ceramic paste is sintered, the Vickers hardness of the ceramic paste is not less than 3GPa, and the chemical solubility is not more than 70μg / cm 2 , fracture toughness not less than 1.0 (MPa) , three-point bending strength is not less than 100 Mpa.

[0012] In the present invention, the ceramic paste contains lithium and strontium elements.

[0013] Specifically, in the present invention, the linear expansion coefficient of the ceramic paste can be adapted to a variety of restorations, thereby ensuring good mechanical properties and use effects. The linear expansion coefficient of common restorations such as metal-based restorations is usually 13.8~14.0×10 -6 / ℃, the linear expansion coefficient of zirconia restoration is 10.5×10-6 / ℃. The linear expansion coefficient of the ceramic paste in the present invention is smaller than the linear expansion coefficient of the above-mentioned repair substrate. Preferably, the difference in linear expansion coefficient between the ceramic paste and the metal base repair body, and between the ceramic paste and the zirconia repair body is (0-4)×10 -6 / ℃ range, more preferably, the difference in linear expansion coefficient is (0-2)×10 -6 / ℃.

[0014] In the present invention, the linear expansion coefficient of the ceramic paste can be adjusted by adjusting the content of the glass powder in the ceramic paste. The linear expansion coefficient of the ceramic paste can be measured by heating the sample from room temperature to the softening point using a thermal analyzer NETZSCH DIL 402CL.

[0015] Furthermore, the inorganic component is glass powder, the lithium element exists in the glass powder in the form of Li2O, the strontium element exists in the glass powder in the form of SrO, and the mass ratio of Li2O to SrO is (0.1~50):1.

[0016] It is worth noting that, in the present invention, by adding an appropriate amount of Li2O and SrO, the glazed surface can have a better gloss, and the restoration has a better aesthetics. At the same time, since Li2O and SrO are added to the ceramic paste of the present invention, the ceramic paste exhibits higher Vickers hardness, higher three-point bending strength, higher fracture toughness and lower chemical solubility.

[0017] Furthermore, the average particle size D50 of the glass powder is 5 μm to 35 μm, preferably 7 μm to 25 μm, and more preferably 8 μm to 20 μm. The "average particle size D50" in the present invention is a median particle size (median diameter) representing the average value of the particles. The average particle size of the substrate glass can be obtained by, for example, using a laser diffraction scattering method, a dynamic light scattering method, a centrifugal sedimentation method, an electrical sensing zone method, a screening method, a photon correlation method, and the like.

[0018] The glass transition temperature (Tg) of the glass powder is preferably 650°C or lower, more preferably 520°C or lower; the softening point of the glass powder is preferably 700°C or lower, more preferably 600°C or lower, and more preferably 550°C or lower.

[0019] The glass transition temperature and softening point of the glass powder can be measured by heating the sample from room temperature to the softening point using a thermal analyzer NETZSCH DIL 402CL.

[0020] Furthermore, the glass powder comprises, in terms of mass percentage: SiO2 51%~68% Al2O3 3%~20% K2O 4%~20% B2O3 5%~17% Na2O 1%~10% ZrO2 0.1%~5% Li2O 0.1%~7% SrO 0.1%~4% The total mass percentage of each component of the glass powder is 100%.

[0021] In the present invention, SiO2: 51~68%, can be selected from 59.94%, 51.6%, 62%, 55%, 57%, 60%, 52%, 68%, 58%, 56%, 51%, 59.64% and the like, but is not limited to the listed values, other values ​​not listed within the range are also applicable.

[0022] Al2O3: 3%~20%, the options are 3%, 7%, 8%, 9%, 9.94%, 10%, 12%, 12.3%, 13.8%, 14%, 18.3%, 20%, etc., but not limited to the listed values, other values ​​not listed within the range are also applicable.

[0023] K2O: 4%~20%. The options are 4%, 8%, 9%, 9.94%, 10%, 11%, 11.8%, 12.6%, 4%, 14.5%, 15%, 15.4%, 18%, 19%, 20%, etc., but are not limited to the listed values. Other values ​​not listed within the range are also applicable.

[0024] At the same time, the K2O raw material can be the metal oxide itself or a metal salt containing potassium, such as chloride, nitrate, carbonate, etc.

[0025] B2O3: 4%~20%, options include 5.8%, 6%, 7.9%, 8%, 9.94%, 10%, 11%, 11.8%, 12%, 14%, 17%, etc., but are not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0026] At the same time, the B2O3 raw material can be the oxide itself, or it can be a boron-containing metal salt or boric acid.

[0027] Na2O: 1%~10%, options include 1.6%, 2%, 3%, 4%, 4.97%, 5%, 8.9%, 9.2%, 9.3%, 10%, etc., but are not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0028] Meanwhile, the Na2O raw material can be the metal oxide itself or a metal salt containing sodium, such as chloride, nitrate, carbonate, etc.

[0029] ZrO2: 0.1%~5%, the options are 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 4.97%, 5%, etc., but not limited to the listed values, other values ​​not listed within the range are also applicable.

[0030] Li2O: 0.1%~7%, the options are 0.1%, 0.2%, 0.5%, 0.6%, 2%, 7%, etc., but not limited to the listed values, other values ​​not listed within the range are also applicable.

[0031] Meanwhile, the SrO raw material may be a metal salt containing strontium, such as chloride, nitrate, and the like.

[0032] SrO: 0.1%~4%, the options are 0.1%, 0.2%, 0.6%, 1%, 1.4%, 4%, etc., but not limited to the listed values, other values ​​not listed within the range are also applicable.

[0033] Meanwhile, the SrO raw material can be a metal salt containing lithium, such as chloride, nitrate, etc.

[0034] Specifically, the method for preparing glass powder with suitable particle size by using the above components can be to calculate the original mass of all raw material oxides or metal salts according to the proportion of the final oxide, heat and melt to a suitable temperature, so that the raw materials are first turned into glass frits, and the heating temperature can be between 500-1500°C. The prepared frits are obtained by using appropriate crushing devices and classification devices to obtain appropriate particle size. The crushing device can be a jaw crusher, a vibrating ball mill, or a planetary grinder; as a classification device, it can be a centrifugal classifier such as a vibrating screen, a cyclone separator, a wet classifier such as a sedimentation classifier, etc.

[0035] The method for preparing glass powder with suitable particle size in the present invention can also be to select some oxide raw materials to melt first, then add some oxide raw materials to mix and crush, and then use a classification device to classify to obtain glass powder with suitable particle size. Since the glass powder is an important raw material for ceramic paste in the present invention, the focus of the present invention is not how to prepare the glass powder, so it will not be repeated here, but for those skilled in the art, the glass powder mentioned in the present invention can be prepared.

[0036] Furthermore, the organic component includes an organic solvent and a dispersant. Based on 100 parts by mass of the glass powder, the mass portion of the organic solvent is 20 parts to 100 parts; the mass portion of the dispersant is 0.01 parts to 5 parts.

[0037] In the present invention, the boiling point of the organic solvent is 180° C. to 300° C., and the organic solvent is one or more of an alcohol solvent, an ester solvent, and an ether solvent.

[0038] Further, based on 100 parts by mass of the organic solvent, the alcohol accounts for 70 to 100 parts; preferably, the alcohol accounts for 85 to 100 parts; more preferably, the alcohol accounts for 90 to 100 parts.

[0039] In the present invention, the alcohol organic solvent can be: 1,2-ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-pentanediol, 1,5-pentanediol, 2,4-pentanediol, 1,2-hexanediol, 2,5-hexanediol, ethylene glycol, diethylene glycol, tetraethylene glycol, polyethylene glycol (molecular weight 200-600), polypropylene glycol, 1-methyl-1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-methyl-1,4-butylene glycol, 3-methyl-1,3-butylene glycol, 2-methyl-1 one or more of 2,4-dimethyl-1-pentanol, 2,4-diethyl-1,5-pentanol, 2-ethyl-1,3-hexanediol, 3-benzyloxy-1,2-propanediol, 4-benzyloxy-1,2-butanediol, 2-heptanol, 3-heptanol, 1-hexanol, 2-hexanol, 3-hexanol, 2-methyl-1-pentanol, 3-methyl-1-pentanol, 4-methyl-1-pentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 2,2-dimethyl-1-butanol, 2-ethyl-1-butanol, 2-phenoxyethanol, glycerol, 1,2,3-butanetriol and 1,2,6-hexanetriol.

[0040] Furthermore, the monohydric alcohols are: 2-heptanol, 3-heptanol, 1-hexanol, 2-hexanol, 3-hexanol, 2-methyl-1-pentanol, 3-methyl-1-pentanol, 4-methyl-1-pentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 2,2-dimethyl-1-butanol, 2-ethyl-1-butanol, and 2-phenoxyethanol.

[0041] Further, the alcohol solvent is a diol solvent; preferably, the diol solvent includes 1,2-ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,2-pentanediol, 1,5-pentanediol, 2,4-pentanediol, 1,2-hexanediol, 2,5-hexanediol, ethylene glycol, diethylene glycol, tetraethylene glycol , polyethylene glycol (molecular weight 200~600), polypropylene glycol, 1-methyl-1,3-propanediol, 2-methyl-1,3-propanediol, 2-methyl-1,4-butanediol, 3-methyl-1,3-butanediol, 2-methyl-2,4-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 3-benzyloxy-1,2-propanediol, and 4-benzyloxy-1,2-butanediol.

[0042] Furthermore, the triols are glycerol, 1,2,3-butanetriol and 1,2,6-hexanetriol.

[0043] In the present invention, the ether organic solvent includes one or more of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, and triethylene glycol monomethyl ether.

[0044] In the present invention, the ester organic solvent includes one or more of ethyl acetate, butyl butyrate, methyl formate, dimethyl phthalate, and diethyl phthalate.

[0045] Furthermore, the dispersant is cellulose ether, and the cellulose ether includes one or both of hydroxyalkyl cellulose ether and hydrophobically modified hydroxyalkyl cellulose ether.

[0046] It is worth noting that the condensation degree of cellulose ether is 100-700000. At the same time, at a temperature below 25°C, the viscosity of cellulose ether is greater than or equal to 100 mPa·s and less than or equal to 5000 mPa·s.

[0047] In the present invention, the hydroxyalkyl cellulose ether includes one or more of hydroxyethyl cellulose (HEC), hydroxypropyl cellulose (HPC), ethyl hydroxyethyl cellulose (EHEC), carboxymethyl cellulose (CMC), carboxymethyl hydroxyethyl cellulose (CMHEC), hydroxypropyl hydroxyethyl cellulose (HPHEC), methyl cellulose (MC), methyl hydroxypropyl cellulose (MHPC), methyl hydroxyethyl cellulose (MHEC), and carboxymethyl methyl cellulose (CMMC).

[0048] Furthermore, the cellulose ether is a hydrophobically modified hydroxyalkyl cellulose ether.

[0049] In the present invention, the hydrophobically modified hydroxyalkyl cellulose ether includes one or any combination of hydrophobically modified carboxymethyl cellulose (HMCMC), hydrophobically modified hydroxyethyl cellulose (HMHEC), hydrophobically modified hydroxypropyl cellulose (HMHPC), hydrophobically modified ethyl hydroxyethyl cellulose (HMEHEC), hydrophobically modified carboxymethyl hydroxyethyl cellulose (HMCMHEC), hydrophobically modified hydroxypropyl hydroxyethyl cellulose (HMHPHEC), hydrophobically modified methyl cellulose (HMMC), hydrophobically modified methyl hydroxypropyl cellulose (HMMHPC), methyl hydroxyethyl cellulose, hydrophobically modified cellulose (HMMHEC), hydrophobically modified carboxymethyl methyl cellulose (HMCMMC), cationic hydroxyethyl cellulose (cationic HEC), and cationic hydrophobically modified hydroxyethyl cellulose (cationic HMHEC).

[0050] It should be noted that the cellulose ethers that can be used for the purpose of the present invention can be prepared by methods known in the art, or any commercially available products, such as NATROSOL 250 HMHEC, NATROSOL 250 HEC B, NATROSOL 250 HHR PC, can also be used.

[0051] Cellulose ether can usually be used as a dispersant. In the present invention, after the ceramic paste with cellulose ether is brushed on the denture restoration and then dried, the glass powder will be firmly bonded to the surface of the restoration, making it easier for the ceramic paste to combine with the substrate. The cellulose ether in the paste can also allow the glass powder particles to be evenly distributed in the organic solvent, ensuring the stable storage and brushing use of the ceramic paste product. The glass powder particles are evenly dispersed in the organic liquid, which is also beneficial to the drying process before sintering. The glass powder particles are densely stacked, and the glaze surface after sintering is smooth, dense and defect-free, and has higher mechanical properties.

[0052] For those skilled in the art, colorants can be added to the paste formula to prepare colored ceramic pastes, which can achieve color finishing of the outer surface of ceramic restorations and production of simulated pattern details on dentures.

[0053] It should be noted that there is no particular limitation on the preparation process of the ceramic paste in the present invention. For those skilled in the art, the raw materials of each component can be weighed according to the formula ratio, mixed evenly to prepare a paste for use. The mixing method can be ball milling mixing, agitator mixing under normal pressure, vacuum stirring mixing, etc.

[0054] When the ceramic paste of the present invention is used, the ceramic paste is mainly used for glazing the outer surface of a dental restoration, and preferably the ceramic paste is used for glazing the outer surface of a ceramic restoration.

[0055] When preparing a ceramic restoration, the ceramic paste prepared by the present invention is coated on a restoration substrate, dried and formed, and then fired.

[0056] There is no particular restriction on the drying and molding conditions. The recommended drying temperature is below 600°C, and the more preferred recommended drying temperature is below 500°C. The recommended drying time is 1 min to 20 min, the preferred time is 2 to 15 min, and the more preferred drying time is 3 to 10 min.

[0057] Drying and molding before sintering is more conducive to the combination of the glaze before sintering on the restoration, which will make the glaze before sintering densely packed and the particles between the glass powder more reasonably arranged. After sintering into glaze, there will be fewer glaze defects.

[0058] There is no special restriction on the heating rate during firing, which can be selected according to the type of porcelain and the volume of the restoration. The preferred heating rate is recommended to be 10~99℃ / min, the preferred heating rate is 20~75℃ / min, and the more preferred heating rate is 25~55℃ / min.

[0059] During the firing heating process, sintering can be performed at room temperature or in vacuum.

[0060] The firing temperature during firing (i.e., the maximum firing temperature) can be selected according to the type of porcelain and the volume of the restoration. The preferred firing temperature is 680°C~1000°C, the further preferred firing temperature is 700°C~950°C, and the further preferred firing temperature is 720°C~850°C.

[0061] The firing temperature holding time during firing (i.e., the holding time of the maximum firing temperature) can be selected according to the type of porcelain and the volume of the restoration. The preferred firing temperature holding time is 0.1 to 45 min, and the further preferred firing temperature holding time is 1 min to 25 min.

[0062] Compared with the prior art, the present invention has the following beneficial effects: (1) By introducing strontium and lithium into the ceramic paste and controlling the mass ratio of Li2O and SrO in the inorganic components to the range of Li2O:SrO=(0.1~50):1, the ceramic paste can have higher hardness, strength and fracture toughness, while reducing the chemical solubility of the ceramic paste; (2) By adding cellulose ether to the ceramic paste, the ceramic paste is more conducive to combining with the glazed restoration, and the powder is more densely packed after drying during the firing process. The sintered glaze has higher Vickers hardness, bending resistance and fracture toughness, and lower chemical solubility. (3) The present invention provides a facing porcelain in the form of a ceramic paste, which eliminates the mixing step compared to traditional single powder facing porcelain powder and is simpler and more convenient to use. DETAILED DESCRIPTION

[0063] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0064] ① Preparation of glass powder As shown in Table 1, in the prepared glass powders 1 to 21, the formula of the glass powder is SiO2: 51%~68%, Al2O3: 3%~20%, K2O: 4%~20%, B2O3: 5%~17%, Na2O: 1%~10%, ZrO2: 0.1%~5%, Li2O: 0.1%~7%, SrO: 0.1%~4%. Except for the difference in the content of each component, the other preparation methods and processes are the same among the glass powders.

[0065] Table 1: Detailed list of glass powder components

[0066] ②Preparation of ceramic paste The glass powder prepared according to Table 1 is mixed with an organic solvent and a cellulose ether to prepare a ceramic paste. Specifically, during the preparation process, the contents of glass powder, organic solvent and cellulose ether are shown in Table 2. At the same time, Table 2 also lists the specific components of the organic solvent and cellulose ether, as well as the three-point bending strength, fracture toughness, chemical solubility and Vickers hardness of the prepared ceramic paste. It should be noted that in Table 2, the ceramic pastes in Examples 1 to 18 and Comparative Examples 1 to 6 have the same preparation method and process except for the different contents of the glass powder, organic solvent and cellulose ether.

[0067] Table 2: Prepared ceramic paste and performance test of ceramic paste

[0068] Table 2

[0069] ③Performance testing Test results: The test results of three-point flexural strength, fracture toughness, chemical solubility and Vickers hardness of ceramic pastes with different compositions are shown in Table 2 above.

[0070] Test basis: <Chemical Solubility Test> Chemical solubility testing is an important basis for evaluating the stable retention of dental ceramic materials in the mouth.

[0071] The test was carried out in accordance with the chemical solubility test requirements specified in GB 30367-2013 “Dental Ceramic Materials”.

[0072] The specific sample preparation method is to apply dental glazing ceramic paste to the front and back sides of a (4±0.1) cm×(4±0.1) cm×(2±0.02) cm zirconia ceramic sheet with a brush thickness of (0.2±0.05) mm, and then sinter and shape the sample according to the method of using the ceramic paste. The total area of ​​the sample coated with glaze that can be freely exposed to the test solution is at least 30 cm 2 The test results are the data of chemical solubility test.

[0073] <Vickers hardness test> The test is carried out in accordance with the test method specified in GB / T 16534-2009 "Test method for room temperature hardness of fine ceramics".

[0074] The specific sample preparation method is to apply the ceramic paste on the surface of the zirconia sheet and then sinter it according to the method of using the ceramic paste. There is no limit to the number of coatings, as long as the thickness of the final ceramic paste film after polishing is not less than 0.5 mm. There is no special restriction on the size of the coated zirconia sheet, as long as the size of the ceramic paste film sample finally prepared meets the requirements of GB / T16534-2009, and the Vickers hardness value of at least 5 effective indentations can be measured. The average value of the measured Vickers hardness value is the Vickers hardness value tested by the present invention.

[0075] The force value selected for the Vickers hardness test of the present invention is 9.807N (1kgf), and the Vickers hardness value obtained by the test is expressed in GPa.

[0076] <Three-point bending strength test> The strength test of dental ceramic paste was carried out according to the three-point bending strength test method recommended in GB 30367-2013 “Dental Ceramic Materials”.

[0077] The specific sample preparation method is as follows: place the dental ceramic paste in a blast drying oven, set the temperature to 100±10℃, dry the liquid, and obtain the solid remaining after the paste is dried; sieve the dried powder evenly, and select 150-200 mesh for the sieve; press the powder into shape in a mold once, and the pressing pressure is between 2-7MPa. There is no special restriction on the size of the mold used for pressing, as long as it can ensure that the ceramic paste block finally sintered is larger than the size of the spline to be processed, and can facilitate the removal of the spline and processing. The block obtained above is subjected to secondary isostatic pressing, and the pressure range is between 230-250MPa. After being pressed into blocks, it is fired and formed according to the method for using the ceramic paste.

[0078] The fired block is processed into splines of (35±0.2) mm×(3±0.2) mm×(4±0.2) mm, with at least 10 splines and preferably 30 splines. The chamfering and surface polishing are performed as required by the standard, and the average value of the test spline data is obtained to obtain the strength data.

[0079] <Fracture toughness test> The fracture toughness test of dental ceramic paste was carried out according to the three-point bending strength test method recommended in Appendix A of GB 30367-2013 “Dental Ceramic Materials”.

[0080] The specific sample preparation method is as follows: place the dental ceramic paste in a blast drying oven, set the temperature to 100±10℃, dry the liquid, and obtain the solid remaining after the paste is dried; sieve the dried powder evenly, and select 150-200 mesh for the sieve; press the powder into shape in a mold once, and the pressing pressure is between 2-7MPa. There is no special restriction on the size of the mold used for pressing, as long as it can ensure that the ceramic paste block finally sintered is larger than the size of the spline to be processed, and it is convenient to take out the spline and process it. The block obtained by the first pressing is subjected to isostatic pressing for a second time, and the pressure range is between 230-250MPa. After being pressed into blocks, it is fired and formed according to the method for using the ceramic paste.

[0081] The sintered block is processed into a specimen of (40±0.2) mm×(3±0.2) mm×(4±0.2) mm, and a V-groove is made on the 3 mm wide surface according to the method recommended in the standard. Five qualified specimens are prepared for testing and the average value of the data is the fracture toughness test data.

[0082] ④Results analysis Compared with Example 1, Comparative Example 1 is different in that the ceramic paste prepared in Comparative Example 1 does not contain cellulose ether. Compared with Example 1, the Vickers hardness, three-dimensional bending strength, and fracture toughness of the ceramic paste prepared in Comparative Example 1 are lower than those of the ceramic paste prepared in Example 1, and the chemical solubility of the ceramic paste prepared in Comparative Example 1 is higher than that of the ceramic paste prepared in Example 1. From the results, it can be seen that the addition of cellulose ether is beneficial to improving strength and fracture toughness and reducing chemical solubility.

[0083] In the ceramic paste prepared in Comparative Example 2, the glass powder used does not contain Li2O and SrO, and the glass powder used in the ceramic pastes prepared in Examples 1-18 all contain Li2O and SrO. The ceramic prepared in Comparative Example 2 was tested, and the Vickers hardness, three-point bending strength and fracture toughness data tested were all lower than the ceramic pastes prepared in Examples 1-18, and the chemical solubility value of the ceramic paste prepared in Comparative Example 2 was greater than that of the ceramic pastes prepared in Examples 1-18. Therefore, without adding Li2O and SrO, the hardness, bending strength and fracture toughness of the ceramic paste cannot be improved, and the chemical solubility cannot be reduced.

[0084] In the ceramic paste prepared in Comparative Example 3, the glass powder used does not contain SrO, and in the ceramic paste prepared in Comparative Example 4, the glass powder used does not contain Li2O. The Vickers hardness, strength and fracture toughness of the ceramic pastes prepared in Comparative Examples 3 and 4 are lower than those prepared in Examples 1 to 18, and the chemical solubility is higher than that of the ceramic pastes prepared in Examples 1 to 18. Therefore, when only Li2O or SrO is added, the technical effect is not as good as that of adding Li2O and SrO at the same time.

[0085] In the ceramic paste prepared in Comparative Example 5, the percentage content of Li2O in the glass powder used is 8%, which exceeds the percentage content in Examples 1 to 18 (0.1% to 7%). Combined with the test results in Table 2, it can be seen that the Vickers hardness, three-point bending strength and fracture toughness are lower than those of the ceramic pastes prepared in Examples 1 to 18, and the chemical solubility is higher than that of the ceramic pastes prepared in Examples 1 to 18.

[0086] In the ceramic paste prepared in Comparative Example 6, the percentage content of SrO in the glass powder used is 5%, which exceeds the percentage content in Examples 1 to 18 (0.1% to 4%). Combined with the test results in Table 2, it can be seen that the Vickers hardness, three-point bending strength and fracture toughness are lower than those of the ceramic pastes prepared in Examples 1 to 18, and the chemical solubility is higher than that of the ceramic pastes prepared in Examples 1 to 18.

[0087] In summary, the simultaneous addition of Li2O and SrO can improve the Vickers hardness, strength and fracture toughness of the ceramic paste and reduce the chemical solubility. In combination with the embodiments and comparative examples in Tables 1 and 2, it can be seen that when the percentage content of Li2O in the glass powder of the ceramic paste is 0.1%~7% and the percentage content of SrO is 0.1%~4%, the Vickers hardness, three-point bending strength and fracture toughness of the obtained ceramic paste are the best, and the chemical solubility is also the lowest. Among them, the Vickers hardness is not less than 3 Gpa and greater than 4 GPa, the three-point bending strength is not less than 100 MPa and greater than 120 MPa, and the fracture toughness is not less than 1.0 (MPa) , and greater than 1.2 (MPa) , chemical solubility is not more than 70μg / cm 2 , and no more than 35μg / cm 2 In addition, the addition of cellulose ether is beneficial to improving Vickers hardness, three-point bending strength, fracture toughness, and reducing chemical solubility.

[0088] GB 30367-2013 Dental Ceramic Materials requires that the minimum strength of metal or ceramic-based aesthetic ceramics and veneer ceramics should be 50 MPa, the minimum fracture toughness requirement should be 0.7, and the maximum chemical solubility should not exceed 100 μg / cm 2 The data tested in Examples 1-18 of the present invention have far exceeded the requirements in the standard, and the effect is obvious.

[0089] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. A ceramic paste for glazing, characterized in that: The ceramic paste for glazing is composed of organic components and inorganic components. After sintering, the Vickers hardness of the glazing paste is not less than 3 GPa and the chemical solubility is not more than 70 μg / cm 2 ; The ceramic paste contains lithium and strontium elements.

2. A ceramic paste for glazing as claimed in claim 1, characterized in that: The inorganic component is glass powder, lithium element exists in the glass powder in the form of Li2O, strontium element exists in the glass powder in the form of SrO, and the mass ratio of Li2O to SrO is (0.1~50):

1.

3. A ceramic paste for glazing as claimed in claim 1, characterized in that: The average particle size D50 of the glass powder is 5μm~35μm; Preferably, 7 μm to 25 μm; More preferably, it is 8μm~20μm.

4. A ceramic paste for glazing as claimed in claim 2, characterized in that: In terms of mass percentage, the glass powder comprises: SiO2 51%~68% Al2O3 3%~20% K2O 4%~20% B2O3 5%~17% Na2O 1%~10% ZrO2 0.1%~5% Li2O 0.1%~7% SrO 0.1%~4% The total mass percentage of each component of the glass powder is 100%.

5. A ceramic paste for glazing as claimed in claim 2, characterized in that: The organic component includes an organic solvent and a dispersant. Based on 100 parts by mass of the glass powder, the mass portion of the organic solvent is 20 parts to 100 parts; the mass portion of the dispersant is 0.01 parts to 5 parts.

6. A ceramic paste for glazing as claimed in claim 5, characterized in that: The boiling point of the organic solvent is 180° C. to 300° C., and the organic solvent is one or more of an alcohol solvent, an ester solvent, and an ether solvent.

7. A ceramic paste for glazing as claimed in claim 6, characterized in that: Calculated relative to 100 parts by mass of the organic solvent, the alcohol accounts for 70 parts to 100 parts; Preferably, the alcohol accounts for 85 to 100 parts; More preferably, the alcohol accounts for 90 to 100 parts.

8. A ceramic paste for glazing as claimed in claim 7, characterized in that: The alcohol solvent is one or more of a monohydric alcohol solvent, a dihydric alcohol solvent and a trihydric alcohol solvent; Preferably, the monohydric alcohols include: 2-heptanol, 3-heptanol, 1-hexanol, 2-hexanol, 3-hexanol, 2-methyl-1-pentanol, 3-methyl-1-pentanol, 4-methyl-1-pentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 2,2-dimethyl-1-butanol, 2-ethyl-1-butanol, 2-phenoxyethanol; Preferably, the diol solvent includes 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2-methyl-2,4-pentanediol, 1,2-pentanediol, and 2-methyl-2,4-pentanediol; Preferably, the triols include: glycerol, 1,2,3-butanetriol and 1,2,6-hexanetriol.

9. A ceramic paste for glazing as claimed in claim 5, characterized in that: The dispersant is cellulose ether; Preferably, the cellulose ether comprises one or both of hydroxyalkyl cellulose ether and hydrophobically modified hydroxyalkyl cellulose ether.

10. A ceramic paste for glazing as claimed in claim 9, characterized in that: The cellulose ether is a hydrophobically modified hydroxyalkyl cellulose ether.

Citation Information

Patent Citations

  • Dental porcelain paste

    CN111467246A

  • Paste-type dental glass composition

    WO2022118905A1

  • Porcelain paste for dentistry

    WO2024024661A1